2010
DOI: 10.1007/s10646-010-0540-x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and DNA damage in the earthworm Eisenia fetida induced by toluene, ethylbenzene and xylene

Abstract: Superoxide dismutase (SOD), guaiacol peroxidase (POD), catalase (CAT), and the comet assay (SCGE) were used as biomarkers to evaluate the oxidative stress and genotoxicity of toluene, ethylbenzene and xylene in earthworms (Eisenia fetida). The results indicated that the exposure of the three pollutants caused a stress response of the three enzymes, an approximate bell-shaped change (a tendency of inducement firstly and then inhibition with increasing concentrations of the pollutants) was mostly found. The thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(25 citation statements)
references
References 52 publications
2
22
1
Order By: Relevance
“…Eisenia fetida have CAT activity increased when reaching a concentration of nanoparticles in an artificial soil Zn 500 mg/kg and decreased at a dose of 1000 mg/kg. A similar effect of Zn NPs was registered by Liu et al (2010). This is possible due to the high activity of catalase in soil substrate and high turnover of metal between the substrate and the body of the worm (Chelikani et al, 2004).…”
Section: Wwwccsenetorg/massupporting
confidence: 65%
“…Eisenia fetida have CAT activity increased when reaching a concentration of nanoparticles in an artificial soil Zn 500 mg/kg and decreased at a dose of 1000 mg/kg. A similar effect of Zn NPs was registered by Liu et al (2010). This is possible due to the high activity of catalase in soil substrate and high turnover of metal between the substrate and the body of the worm (Chelikani et al, 2004).…”
Section: Wwwccsenetorg/massupporting
confidence: 65%
“…While interpreting these outcomes, it seems reasonable to assume that increased activities of antioxidant enzymes might be indicative of increased oxidative stress, possibly caused by an occupational exposure of nail technicians. Indeed, exacerbation of oxidative stress has already been implicated in mechanisms underlying the effects exerted by the low-level exposure to VOC in both the animal models (22,45) and human subjects (10,11,46). Notwithstanding, the above-mentioned lack of any significant changes in levels of TBARS and DNA strand breaks between nail technicians and control subjects seems to contradict this thesis.…”
Section: Grešner Et Almentioning
confidence: 98%
“…Even though these substances are considered to be neither carcinogenic nor genotoxic to humans (IARC class 3 carcinogens, ie, not classifiable as to their carcinogenicity to humans), there is a growing amount of evidence suggesting increased (i) levels of markers of oxidative stress (10)(11)(12), (ii) rate of chromosomal aberrations or sister chromatid exchange (12)(13)(14), and (iii) incidence of various cancers among workers occupationally exposed to toluene or xylene [even at occupational exposures far below the respective occupational limits (15)(16)(17)(18)(19)(20)(21)]. Although precise mechanisms underlying the effects of toluene and xylene remain unknown, the role of oxidative stress, oxidative DNA damage and dysregulated cellular antioxidant levels have been implicated (22)(23)(24). Methacrylates, another group of chemicals used in nail industry, are known sensitizers and were found to give positive results for in vitro genotoxicity, although in vivo outcomes are inconclusive (25,26).…”
mentioning
confidence: 99%
“…The glutathione reductase enzyme also plays an important role in cellular protection by reducing glutathione in the oxidized form (GSSG) to GSH (reduced and active form). Several studies (Liu et al, 2010) indicate that exposure to either organic or inorganic pollutants are able to induce a stress response in the antioxidant enzymes, suggesting their potential application as general biomarkers for assessing effects of pollutants in terrestrial ecosystems at early stages and with low concentrations. However, the dose-dependent and time-dependent response of antioxidant enzymes to pollutant exposure is sometimes complex and a better understanding of their behaviour in stress condition is needed for their application in monitoring and assessment programmes.…”
Section: Antioxidant Enzymesmentioning
confidence: 99%
“…However, the dose-dependent and time-dependent response of antioxidant enzymes to pollutant exposure is sometimes complex and a better understanding of their behaviour in stress condition is needed for their application in monitoring and assessment programmes. For example Liu et al (2010) demonstrated that exposure to toluene, ethylbenzene and xylene in earthworms (Eisenia fetida) induced a bellshaped change in superoxide dismutase and catalase activities with a tendency of inducement firstly and then inhibition with increasing concentrations of the pollutants. Moreover, Wu et al (2011) found superoxide dismutase to be induced during the early period of phenanthrene exposure while with longer exposure times its activity decreased.…”
Section: Antioxidant Enzymesmentioning
confidence: 99%